Una lección de numismática para el joven Felipe II: El Monetario de Filippo Archinto (1540) - Gonzalo Sánchez-Molero, José Luis; Francisco Olmos, José María de (Revista General de Información y Documentación, 2007)
In this work studies a part of the education that received prince Felipe before raising the throne, in particular the related whit to the Numismatist, as much in which it talks about to the concrete pieces, in special those that Archinto bishop sent to him from Italy, as the books and medals related to them and the study of the old times through the images that appear in them. In addition it has been tried to locate in Monetary of the Monastery of San Lorenzo of the Escorial the pieces sent by Archinto, obtaining to identify some of the same ones.
Keywords: Philip II of Spain; Education; Numismatist; Monastery of San Lorenzo of the Escorial; Library; Monetary; Bishop Filippo Archinto